Impact of CEO transition announcement, CEO characteristics and moderating effect of CEO transition plan on share price of Malaysian companies - Sivapregasam, Shubasini (2020)
The rate of Chief Executive Officer (CEO) succession or transition, especially CEO turnover in emerging economies, has increased lately and this has led to growing concerns and worries among investors over the safety, and more importantly, the profitability of their investment in the affected firms. This is especially important for firms with economic exposure to the Covid-19 pandemic as the situation would require the right person to maneuver the firm in the right direction. There have been some empirical studies on CEO succession, but most of such studies have been conducted in developed nations with findings that are largely inconsistent. In addition, studies on announcement effect of CEO succession on the share price are insufficient and biased towards announcement effect on CEO turnover. In view of these worries, this study examines the reaction of share price based on a revised classification of CEO planned succession announcement (Objective 1). It also looks at the CEO characteristics and the moderating effect of the CEO succession plan (CP) as important factors in the share price reaction (Objective 2 and 3). This study is grounded in the theory of efficient market hypothesis (EMH), and examines the share price changes due to CEO turnover and appointment announcement using the standard abnormal return (AR) calculation. The share price reaction, which is referred to as cumulative average abnormal return (CAAR), is estimated using the Capital Asset Pricing Model (CAPM). Next, the impact of the CEO characteristics, which are age, origin, education, experience, stock ownership and gender, against CAAR, is examined using cross-sectional regression analysis. This analysis is conducted across the revised planned and unplanned announcement criteria. Using the similar regression analysis method, an analysis is made on the general announcement type of CEO turnover and appointment. Looking at announcement type separately, the moderating effect of CP on the relationship between the CEO characteristics and the share price reaction is examined. This study uses secondary data from Bursa Malaysia for a period of 10 years, from 2007 to 2016. The CAAR is observed to be significant and positive for planned CEO turnover and appointment announcement, indicating investors’ confidence level with the firm increases with the establishment of a CP. In other words, when announcement of CEO turnover and appointment are made on the same day, it induces a positive reaction to the firm’s share price. As for the impact of CEO characteristics, significant results are found for different characteristics on different event windows. In planned CEO appointment and turnover announcement, origin, education and stock ownership variables are found to be significant. However, this reaction cannot be matched with the type of announcement because both the CEO appointment and turnover announcement occur on the same day. Meanwhile, for unplanned CEO appointment announcement, age, experience and stock ownership variables are significant; whereas for unplanned CEO turnover announcement, origin, education and gender variables are significant. When the CP is moderated in the relationship between CEO characteristics and the share price, age, origin, experience and stock ownership variables are significant for announcement of CEO appointment. In general, when the share price is observed by the general classification of announcement. The CP significantly moderates moderates age, experience and stock ownership for announcement of CEO appointment. The CP also moderates origin and education moderate for announcement of CEO turnover. These findings highlight the importance of CP on firm value. It also emphasises the importance of CEO characteristics, even during his or her removal. The results of this study are expected to contribute to bridging the gaps in the literature on CEO succession by reclassifying announcement types while investigating CEO characteristics. Therefore, it will allow policymakers to re-examine current policies on CEO succession and establish an appropriate CEO succession policy, thus minimising repercussions caused by the sudden removal of a CEO.